Surveys of Australian economics - Gruen, F. H.; Academy of the Social Sciences in Australia (Sydney ; Boston : George Allen & Unwin, 1978)
The book analyses key areas of economic policy. Issues examined include the money supply/price/economic activity nexus, the unemployment/inflation trade off, wages indexation and incomes policies, domestic versus imported inflation, monetary policy and the balance of payments, the tariff compensation debate, the 'Gregory' thesis, the costs of protection, the effects of the 25% tariff cut, agricultural adjustment and stabilisation policies.
Includes bibliographies.
rpm 14/06/2017
Loans
Keywords: Australian -- Economic conditions; Australia--Economic policy; Australia $1 (BEconomic policy $1 (BAddresses, essays, lectures.s; Australia $1 (BEconomic policies $1 (BReviews of researchs; Australia